Geometrically non-linear analysis of rectangular plates on elastic foundation by the coupling of the polynomial differential quadrature (PDQ) and finite difference(FD) methods - Civalek, Örner; Ülker, Mehmet (My University, 2006)
Geometrically nonlinear static and dynamic analysis of rectangular plates resting on elastic foundation are made by the coupling of the polynomial differential quadrature (PDQ)-finite differences (FD) methods. The weighting coefficients for differential quadrature are obtained using the harmonic functions as the test function. The governing differential equations are reduced to a linear algebraic equations in terms of the unknown function values at the grid points in the field domain via differential quadrature for space domains and finite differences methods for time domain. The obtained results are then compared, when possible, with the other results in the related literature. It is found that the obtained results are suitable in point of view the engineering analysis concept.
Polinomal diferansiyel quadrature(PDQ) ve sonlu farklar (SF) metod çifti ile elastik zemine oturan dikdörtgen plaklarm geometrik bakimdan lineer olmayan analizi
Keywords: Differential equations; Elasticity; Finite difference method; Harmonic analysis; Linear equations; Polynomials; Elastic foundation; Harmonic functions; Linear algebraic equations; Polynomial differential quadrature (PDQ); Plates (structural components)